Air-stable and reusable nickel phosphide nanoparticle catalyst for the highly selective hydrogenation of d-glucose to d-sorbitol. Issue 5 (29th January 2021) - Yamaguchi, Sho; Fujita, Shu; Nakajima, Kiyotaka; Yamazoe, Seiji; Yamasaki, Jun; Mizugaki, Tomoo; Mitsudome, Takato
Abstract : An efficient and sustainable d -sorbitol production via d -glucose hydrogenation was achieved over a hydrotalcite-supported nickel phosphide nanoparticle catalyst with stability, high activity and reusability. Abstract : The hydrogenation of carbohydrates to polyols is an industrially important process, but it requires air-unstable, non-noble metal catalysts with low activity and harsh reaction conditions. Herein, we report a hydrotalcite (HT)-supported nickel phosphide nanoparticle (nano-Ni2 P/HT) that exhibits both air stability and high activity for the selective hydrogenation of d -glucose to d -sorbitol in water. The nano-Ni2 P/HT catalyst provides d -sorbitol in excellent yield with >99% selectivity under mild reaction conditions, and is the first non-noble metal catalyst that can operate under just 1 bar of H2 or at ambient temperature. This high-performance nano-Ni2 P/HT catalyst is significantly different from conventional Ni(0) and NiO nanoparticles and Raney catalysts, which result in almost no production of d -sorbitol, demonstrating the unique catalysis of nano-Ni2 P/HT. Furthermore, nano-Ni2 P/HT shows the highest activity among those reported for non-noble metal catalysts. The nano-Ni2 P/HT catalyst can also be reused without sacrificing its high activity and selectivity. Additionally, the successful transformation of a concentrated d -glucose solution (50 wt%) to d -sorbitol has been achieved. This is the first example of an air-stable, highly active, and reusable non-noble metal catalyst that can replace conventional catalysts used for d -sorbitol production, thus providing a cheap, green, and sustainable route for this process.